A study of folk heroism in World War II: The history of the marking’s guerrillas (1942-1945) - Wong, Bennett Jason F. (Animo Repository, 2022)
The current study focuses on the history of the Marking’s Guerrillas and the suitability of the leaders of the guerrilla unit to be labeled as folk heroes through their fame in the Second World War, as their stories suggest after the war. The author aims to study the leaders of Marking’s Guerrillas, the couple Marcos “Marking” V. Agustin and Valeria “Yay” Panlilio. Guided by the inclusive approach, this study investigates the social environment of both leaders to understand their heroism and how they came to be labeled as such. Folk heroes here are defined as people recognized by society to be symbols of good yet outside the law. They often emerge as characters who are defenders of the oppressed or representatives of the minority. This paper demonstrates how the couple received renown for leading the “Marking’s Guerrillas” Yay Regiment against the Japanese invaders by their actions during and their testimonies after the war. Their most vaunted accomplishment was the victory at the Battle of Ipo Dam on May 19, 1945, where they, along with the 43rd Division and the 5th Air Force, secured a decisive victory, wresting control of the water reservoir from the Japanese. This study also distinguishes the Marking’s Guerrillas’ role as a unit during the Second World War. It also analyzes the couple’s suitability to be considered as folk heroes and its importance to the larger context of Philippine World-War II history.